Comportamiento al desgaste de un acero AISI 304 - Alvarez, Patricia; Ruzzante, José Evaristo; Vosen, J.; Fernandez, H.; Hey, Alfredo Martín; Gestido. G. (Comisión Nacional de Energía Atómica; Argentina, 1986)
Fil: Alvarez, Patricia Comisión Nacional de Energía Atómica; Argentina